Rancang Bangun Purwarupa Penerima Paket APRS Berbasis Raspberry Pi 2 untuk Stasiun Bumi - Agfianto Eko Putra; Unggul Adhi Nugroho; Bakhtiar Alldino Ardi Sumbada; Catur Atmaji (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2019)
The design of Raspberry Pi 2-based APRS packets for UGM earth stations has been designed, which is much cheaper than commercial devices on the market. A TV tuner is used as a signal receiver, the receiver is accessed via a laptop wirelessly. A directed antenna with a controller is used to automatically point to the satellite. The test was carried out by receiving the APRS package emitted by the International Space Station (ISS) satellite and the LAPAN-A2 satellite. The results showed that the tool was able to get the ISS satellite APRS package with a total of 6 packages out of 10 packets emitted. The package received has an average amplitude of 1,200 Hz and 2,200 Hz which is much smaller than the overall audio amplitude. This indicates that there is high noise in the signal. While the APRS package from the LAPAN-A2 satellite has not been successfully obtained.